2019–2020 Florida Citrus Production Guide: Phytophthora Foot Rot and Root Rot - Megan M. Dewdney; Evan G. Johnson; James H. Graham (EDIS)
This 7-page fact sheet is part of the 2019–2020 Florida Citrus Production Guide. Written by Megan M. Dewdney, Evan G. Johnson, and James H. Graham, and published by the Plant Pathology Department, April 2019.